2012
DOI: 10.1172/jci64057
|View full text |Cite
|
Sign up to set email alerts
|

Nanog signaling in cancer promotes stem-like phenotype and immune evasion

Abstract: Adaptation of tumor cells to the host is a major cause of cancer progression, failure of therapy, and ultimately death. Immune selection drives this adaptation in human cancer by enriching tumor cells with a cancer stem cell-like (CSC-like) phenotype that makes them resistant to CTL-mediated apoptosis; however, the mechanisms that mediate CSC maintenance and proliferation are largely unknown. Here, we report that CTL-mediated immune selection drives the evolution of tumor cells toward a CSC-like phenotype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(233 citation statements)
references
References 43 publications
(39 reference statements)
8
223
1
1
Order By: Relevance
“…Cancer cells are highly heterogeneous and a small fraction of cancer cells with stem cell properties, known as tumor-initiating cells, or cancer stem cells (CSC), may be responsible for tumorigenesis (2), angiogenesis (3) and metastasis (4). Recently, selection by adaptive immunity has been shown to generate or enrich cancer cells with stemness (5)(6)(7)(8)(9), suggesting the presence of intimate interaction between CSCs and the skewed adaptive immunity in patients with cancer. However, the role of innate immunity in affecting CSCs and their metastasis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells are highly heterogeneous and a small fraction of cancer cells with stem cell properties, known as tumor-initiating cells, or cancer stem cells (CSC), may be responsible for tumorigenesis (2), angiogenesis (3) and metastasis (4). Recently, selection by adaptive immunity has been shown to generate or enrich cancer cells with stemness (5)(6)(7)(8)(9), suggesting the presence of intimate interaction between CSCs and the skewed adaptive immunity in patients with cancer. However, the role of innate immunity in affecting CSCs and their metastasis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that immunoevasion is restricted to CSCs, enabling them to survive in the host (13)(14)(15). Recently, ABCB5 þ malignant melanoma-initiating cells were found to modulate antitumor immunity by preferentially inhibiting IL2-dependent T-cell activation and promoting induction of regulatory T cells (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…Oct4 and Nanog are expressed mainly in embryonic stem cells and only in very low levels in normal adult tissues (42)(43)(44). However, an increasing number of studies demonstrate that both Oct4 and Nanog are aberrantly overexpressed in different types of cancer, contributing to the stem-cell phenotype of tumor cells (45,46). Consistently, it has been demonstrated that overexpression of Oct4 and Nanog in epithelial cells promotes tumorigenesis and metastasis (47,48).…”
Section: Discussionmentioning
confidence: 92%